2019
DOI: 10.5802/smai-jcm.52
|View full text |Cite
|
Sign up to set email alerts
|

Isogeometric analysis with $C^1$ functions on planar, unstructured quadrilateral meshes

Abstract: In the context of isogeometric analysis, globally C 1 isogeometric spaces over unstructured quadrilateral meshes allow the direct solution of fourth order partial differential equations on complex geometries via their Galerkin discretization. The design of such smooth spaces has been intensively studied in the last five years, in particular for the case of planar domains, and is still task of current research. In this paper, we first give a short survey of the developed methods and especially focus on the appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…The only viable approach has been, until now, the use of spline basis on unstructured hexahedral (or tetrahedral) meshes, which has been object of several contributions [38,59,61,63]. In this context, the presence of extraordinary points and edges make the construction of regular B-spline functions preserving accuracy extremely challenging (see [62,33] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The only viable approach has been, until now, the use of spline basis on unstructured hexahedral (or tetrahedral) meshes, which has been object of several contributions [38,59,61,63]. In this context, the presence of extraordinary points and edges make the construction of regular B-spline functions preserving accuracy extremely challenging (see [62,33] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed construction will work uniformly for all possible multi-patch configurations and is much simpler as for the entire C s -smooth space V s . Thereby, the design of the subspace W s will be based on the results of the two-patch case, and is motivated by the methods [27,28] and [32,33], where similar subspaces have been generated for a global smoothness of s = 1 and s = 2, respectively. There, it has been numerically shown that the corresponding subspaces possess as the entire C s -smooth space V s optimal approximation properties.…”
Section: S -Smooth Isogeometric Spaces Over Multi-patch Domainsmentioning
confidence: 99%
“…To generate the vertex subspaces W s Ξ (i) , we will distinguish between different types of vertices Ξ (i) , namely between inner and boundary vertices, and in the latter case also between boundary vertices of patch valency v i ≥ 3, v i = 2 and v i = 1. We will follow a similar approach as used in [27,28] and [32,33] for the construction of C 1 and C 2 -smooth isogeometric spline functions in the vicinity of the vertex Ξ (i) .…”
Section: The Vertex Subspacesmentioning
confidence: 99%
“…[11,12], and general quadrilateral meshes of arbitrary topology [9,10,48]. The recent survey article [29] provides more details about the single methods of the three approaches and also includes further possible constructions.…”
Section: Introductionmentioning
confidence: 99%